Synthesis and Characterization of Reduced Graphene Oxide from Fiber of Borassus Flabelifer by Activation Method - Fandi Angga Prasetya; Ufafa Anggarini; Salim Mustofa; Syarifatus Sholihah; Fathur Iqbal; Hanafi Hanafi; Dode Bara Septyano (Lambung Mangkurat University Press, 2019)
Reduced Graphene Oxide (RGO) has been successfully synthesized by calcination process at 4000C for 4 hours followed by activation with NaOH 1 M. Carbonization is the last process with variations in heating at 6500C, 7500C, 8500C, and 9500C for 1 hour (heating rate 100C / minute). DSC-TGA data shows that there is advanced decomposition at high temperatures, this is confirmed by SEM data which shows the amount of porosity which is getting higher with a size that decreases with temperature. XRD data shows phase differences at low temperatures with a trend of higher levels of crystallinity at high temperatures. Raman spectroscopy data showed an ID / IG ratio of 2.607 and 1.007 on Borassus Flabelifer L with carbonization at 6500C and 9500C respectively. The ID / IG value which is getting closer to 1 indicates that the carbon available in Borassus Flabelifer L has undergone phase changes such as Graphene with a little Oxide commonly called RGO